2013
DOI: 10.4161/jkst.25763
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-STAT3 signaling and premature senescence

Abstract: Cytokines play several roles in developing and/or reinforcing premature cellular senescence of young cells. One such cytokine, interleukin-6 (IL-6), regulates senescence in some systems in addition to its known functions of immune regulation and promotion of tumorigenesis. In this review, we describe recent advances in studies on the roles of IL-6 and its downstream signal transducer and activator of transcription 3 (STAT3) in regulating premature cellular senescence. IL-6/sIL-6Rα stimulation forms a senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(114 citation statements)
references
References 87 publications
8
103
0
3
Order By: Relevance
“…Aging‐related increase in levels of circulatory IL‐6 has been previously reported in humans and mice, and IL‐6 has been proposed as one of the factors contributing to age‐related decline in organism function (Washington et al ., 2011). The role of IL‐6 in cellular senescence has also been demonstrated (Kojima et al ., 2013). It remains to be established whether the effects of IL‐6 on miR‐143:Igfbp5 interactions are maintained in vivo and whether these indeed contribute to defective muscle regeneration during aging.…”
Section: Discussionmentioning
confidence: 99%
“…Aging‐related increase in levels of circulatory IL‐6 has been previously reported in humans and mice, and IL‐6 has been proposed as one of the factors contributing to age‐related decline in organism function (Washington et al ., 2011). The role of IL‐6 in cellular senescence has also been demonstrated (Kojima et al ., 2013). It remains to be established whether the effects of IL‐6 on miR‐143:Igfbp5 interactions are maintained in vivo and whether these indeed contribute to defective muscle regeneration during aging.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 acts on cells as a dimer by binding to a specific IL-6 receptor (IL-6R) complex composed of two IL-6Rα chains (also known as IL-6Rα, gp80 or CD126) and the resultant IL-6/IL-6Rα complex associates with two signal-generating receptor beta chain subunits, named gp130 (also known as IL-6Rβ or CD130), at three distinct receptor-binding sites (Kojima et al 2013). In contrast to gp130, IL-6Rα is only expressed on a limited number of cell types, which actually facilitates the selective activation of several target cells .…”
Section: Biology and Functions Of Il-6mentioning
confidence: 99%
“…IL-6 production has previously been linked to stressinduced premature senescence (SIPS)/replicative senescence and the senescence-associated secretory phenotype (SASP). 48,49 A recent study by Lagerge and colleagues indicated that mTOR inhibition with rapamycin or knockdown of mTOR components causes decreased IL-6/cytokine production in senescent fibroblasts. 50 Although we observed the opposite effect, with increased IL-6 and IL-8 production, our system used proliferating Figure 5.…”
Section: Genesetmentioning
confidence: 99%